Posttraumatic stress symptoms and alcohol outcomes for at-Risk college students: the mediating role of drinking motives and protective behavioral strategies. (4th March 2023) - Jordan, Hallie R.; Madson, Michael B.; Mohn, Richard S.; Dahlen, Eric R.; Nicholson, Bonnie C.; Hoover, Skyler M.
Abstract: The present study evaluated the roles of drinking motives (i.e. social, enhancement, coping, conformity) and alcohol protective behavioral strategy (PBS) subtypes (i.e. serious harm reduction [SHR], stopping/limiting drinking [SLD], manner of drinking [MOD]) as mediators of the relationship between posttraumatic stress symptoms and alcohol-related outcomes (i.e. hazardous drinking, negative consequences) in college students, as well as whether these relationships were invariant by gender. Participants were 492 (50.8% men) college students who reported consuming alcohol at least once in the past 30 days and experiencing at least one potentially traumatic event during their lifetime. Students completed measures of posttraumatic stress symptoms, drinking motives, PBS, hazardous drinking, and alcohol-related negative consequences through an online survey. The positive relationship between posttraumatic stress symptoms and hazardous drinking was partially mediated by coping and enhancement motives independently and sequentially mediated by social motives and two types of PBS (i.e. SHR, SLD) as well as enhancement motives and SHR. Further, the positive relationship between posttraumatic stress symptoms and negative consequences was partially mediated by coping motives, as well as sequentially by enhancement and conformity motives through SHR. Invariance testing revealed that the models were not statistically different across gender. Results suggest types of drinking motives and PBS function differentially in the relationships between posttraumatic stress symptoms and alcohol-related outcomes.